2020
DOI: 10.1186/s12909-020-02330-y
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills teaching and learning in Nepal; what are medical students’ perceptions and experiences? A qualitative study

Abstract: Background Communication skills (CS) are vital for doctors. Indeed, as the most important element of consultations, are highly valued by patients. CS are core, teachable skills, however, have not been widely taught in South Asian medical schools, unlike their western counterparts. Patan Academy of Health Sciences, is one of the first in Nepal to have CS central to its’ aims and curriculum. CS are taught from the first weeks of medical school and re-enforced during preclinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…It is interesting to note that this type of preference is reported regardless of the educational systems pursued. A. H. Douglas et al, in their study, showed that most medical students in Nepal report a need for in-depth DBN education [ 9 ]. In a study by L. A. Díaz-Martínez, only 3.3% of Colombian students reported that they would not be interested in a course to improve competence in DBN [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that this type of preference is reported regardless of the educational systems pursued. A. H. Douglas et al, in their study, showed that most medical students in Nepal report a need for in-depth DBN education [ 9 ]. In a study by L. A. Díaz-Martínez, only 3.3% of Colombian students reported that they would not be interested in a course to improve competence in DBN [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many analyses have revealed the educational effectiveness of training provided in this area [ 6 , 7 ]. However, still not enough students in the course of their education receive formal training developing skills related to DBN [ 8 , 9 ]. In their international study, A. Alshami et al showed that only 26.6% of medical students received formal DBN training during their education [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study comprises part of a qualitative CS curriculum evaluation. Participants’ experiences and perceptions of this CS curriculum were explored in an earlier study [ 45 ]. This paper seeks to explore students’ experiences of CS learning through role modelling in this context.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do this, they need competence in various theoretical, practical, clinical as well as soft skills like counselling and communication. 1 Every part of medical course is important to produce competent graduates. This has called for the design of competency-based curriculum, focusing on variety of learning methods like didactic lectures, problem based learning, videos, simulation, skills laboratory, demonstrations, history taking, patient examinations, laboratory exercises etc.…”
mentioning
confidence: 99%